Electronic spectroscopy of PAHs and PAH derivatives in supersonic jet. Issue Volume 15:Issue S350(2019) (April 2019) - Bejaoui, Salma; Salama, Farid
Abstract: Polycyclic Aromatic Hydrocarbon (PAHs) molecules are attracting much attention in the astrophysical and astrochemical communities because of their ubiquitous presence in space due to their ability to survive in the harsh environmental conditions of the interstellar medium (ISM). The objective of this work is to provide gas phase, high-resolution spectroscopic data on the electronic and vibronic transitions of PAHs and their nitrogenated derivatives measured in astrophysically relevant conditions.